2016
DOI: 10.9734/bjesbs/2016/20140
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Domestic Violence among Married Women in Zambia

Abstract: The objective of the study was to analyze and determine the factors associated with different types of domestic violence (physical, emotional and sexual) in Zambia. The data for the study was derived from the Zambia Demographic Health Survey carried out by Central Statistical Office in 2007. The study was based on a sample of 7146 married women. Data was analyzed using Bivariate and Binary Logistic Regression. The results indicated that 43%, 23% and 15% of respondents reported having experienced physical viole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
(24 reference statements)
6
12
0
Order By: Relevance
“…Another study conducted on Demographic Health Survey in Ghana shows a relatively lower prevalence of domestic violence where 33.6% of women experience it at some point in their life (5). This result is comparable with a study conducted on the Zambian Demographic Health Survey where 43% of women experienced domestic violence (6).…”
Section: Introductionsupporting
confidence: 85%
“…Another study conducted on Demographic Health Survey in Ghana shows a relatively lower prevalence of domestic violence where 33.6% of women experience it at some point in their life (5). This result is comparable with a study conducted on the Zambian Demographic Health Survey where 43% of women experienced domestic violence (6).…”
Section: Introductionsupporting
confidence: 85%
“…However, the relationship between physical violence and marital duration is culture sensitive. For example, Kusanthan et al (2016) found the opposite result among Zambian women, where the prevalence of physical violence increased with increased marital duration. Non-users of contraceptives were found to be less exposed to physical violence compared with current users.…”
Section: Discussionmentioning
confidence: 93%
“…According to the empirical findings obtained in the study; (i) the risk of facing physical, sexual and both physical and sexual violence by the participants who lived in the Eastern region of the country was higher than those who lived in other regions; (ii) the probability of facing physical violence in women between 43-59 years of age was higher than those of other age groups; (iii) the rate of women who received no education in terms of facing violence was higher than those from other educational levels; (iv) the probability of facing violence by women whose spouses were graduated from secondary schools was higher than those whose spouses were from other educational levels; (v) the probability of facing violence by women whose spouses worked at industrial sector was lower than the women whose spouses worked at other sectors; (vi) the increase in the frequency of alcohol use and gambling of the husband increased the probability of facing physical and sexual violence of women; (vii) the probability of facing physical, sexual and both physical and sexual violence was higher in women who think that their spouses were cheating them; (viii) the probability of facing physical and sexual violence against women who were relatives with their spouses was higher than women who were not relatives with their husbands; (ix) the probability of facing physical and sexual violence for women whose husbands did not receive any education was higher than women whose husbands were from other educational levels. Ksuthan, Mwaba and Menon (2016) conducted a study for Zambia and analyzed the factors that affected domestic violence with the Logistic Regression Model. The sampling of the study included 7146 ever married women.…”
Section: Literature Reviewmentioning
confidence: 99%